A Computer-Directed Geographic Coastal Use Classification System for Ecologic Planning: The Case of the Florida Keys - Gustavo A. Antonini; Leonard Zobler; Robert Swett (EDIS)
SGR-102, a 104-page illustrated report by Gustavo A. Antonini, Leonard Zobler, and Robert Swett, presents a baywater assimilation-capacity approach to coastal zone management, using the Florida Keys (Stock Island) as a case study. Originally published April 1992 by the Florida Sea Grant College Program. Reviewed March 2008.